Melt Electrospinning : a Green Method to Produce Superfine Fibers - Liu, Yong (Academic Press, 2019)
Melt Electrospinning: A Green Method to Produce Superfine Fibers introduces the latest results from a leading research group in this area, exploring the structure, equipment polymer properties and spinning conditions of melt electrospinning. Sections introduce the invention of melt electrospinning, including the independent development of centrifugal melt electrospinning and upward melt electrospinning, discuss electro magnetization of melt and the testing method of fiber performance by means of different polymers and self-designed devices, cover simulation, and introduce principle methods and improvement measures of centrifugal melt electrospinning.
Keywords: Electrospinning.; elektronické knihy; electronic books